ANALISIS PENERAPAN PRINSIP GOOD GOVERNANCE DALAM PELAYANAN PUBLIK DI DESA NARIMBANG MULIA KECAMATAN RANGKASBITUNG - Maryanti, Siti; Bangsawan, Try Adhi; Amilia, Rizki (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2025)
The results of the study show that the principles of accountability, openness, and rule of law have been implemented quite well, although there are still weaknesses in terms of transparency, particularly in the use of village websites, which have not been optimally utilized as a means of digital public service. Factors supporting implementation include effective communication, the availability of competent human resources, the honest and democratic attitude of officials, clear SOP-based program mechanisms, and an organizational structure that supports village governance. Meanwhile, the obstacles found include internal barriers such as the lack of understanding of good governance principles among officials and a lack of discipline during working hours, as well as external barriers in the form of low community participation and limited community understanding of technology-based services.